EFFECT OF REWARD SYSTEM, WORK ENVIRONMENT, AND EMPOWERMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH EMPLOYEE ENGAGEMENT IN COAL UTILITY UNIT OF PT. PETROCHEMICAL GRESIK - Ben Manggar Imawan; Qausya Faviandhani (Jurnal Ekonomi, 2018)
This study aims to explore the performance of PT Petrokimia Gresik Coal Utility Unit employees who have recently emerged issues regarding employee performance that seem to have decreased so that testing is needed to prove whether the employee's performance has decreased. Exploration of employee performance is carried out using quantitative research methods, with the analysis technique using Path Analysis. By distributing several questionnaires to 40 employees who work in the Coal Utility Unit, to find out the results of the analysis required several tests such as the Validity Test which states valid, because the correlation value of each question item is greater than its critical value and for the Reliability Test it reaches Cronbach numbers. alpha 0.892 and above 0.60, it is declared reliable and trustworthy. With the results of the calculations that have been done, it can be seen that the contribution of the Reward System, Work Environment and Empowerment variables affects the Employee Engagement and Organizational Citizenship Behavior variables as a measuring factor for employee performance.